Indication for and outcomes of continuous Positive Airways Pressure (CPAP) and High Flow Nasal Cannula oxygen therapy (HFNC) in children admitted to Red Cross War Memorial's Hospital (RCWMCH) excluding those with primary respiratory aetiologies - Browde, Kate (Department of Paediatrics and Child Health, 2017)
Aim: Noninvasive Continuous Positive Airway Pressure (nCPAP) and High Flow Nasal Cannula oxygen therapy (HFNC) are non-invasive ventilation (NIV) modalities appropriate for children in developing countries. There is minimal literature describing nCPAP and HFNC use in children with respiratory compromise secondary to non-pulmonary disease. This study aimed to describe the characteristics and outcomes of all children without primary lung pathology, who received nCPAP and HFNC during their admission to Red Cross War Memorial Children's Hospital, Cape Town, South Africa. Methods: This was a prospective observational study of routinely collected data, between August 2015 and January 2016. Primary and secondary outcome measures were NIV failure (progression to intubation and invasive ventilation) and Paediatric Intensive Care Unit (PICU) admission respectively. Comparative statistics were conducted using Mann-Whitney U tests. Data significantly associated with the primary and secondary outcomes on univariate analysis were entered into backward stepwise logistic regression models to determine independent predictive factors. Results: There were 31 cases of nCPAP and one case of HFNC use in 31 patients (median (IQR) age 3.5 (1.8 – 7.6) months. The majority (n=23; 71.9%) presented with primary diarrhoeal disease. There were two deaths (6.5%), 17 (53.1%) Paediatric Intensive Care (PICU) admissions, and five (15.6%) cases received invasive ventilation (NIV failure). Median (IQR) duration of hospital stay was 11.50 (6.0 – 17.5) days. Patients who failed NIV had lower admission SaO2 than those without treatment failure (95 (95-99)% vs 100 (100-100)%; p = 0.03). On multiple logistic regression, lower temperature (OR 0.19; 95% CI 0.05 – 0.78; p = 0.02) and receiving inotropes in the emergency setting, (OR 23.05; 95% CI 1.64 – 325.06; p = 0.02) were independently associated with PICU admission. Conclusions: nCPAP is used clinically for the management of children with respiratory compromise secondary to non-pulmonary illnesses, particularly diarrhoeal disease. Larger controlled clinical studies are needed to determine the effectiveness and utility of nCPAP in this population. HFNC was not commonly used, and this modality requires further investigation in this population.